Traditional Chinese Medicine nursing management for rheumatoid arthritis patients with damp-heat arthralgia spasm syndrome (类风湿关节炎湿热痹阻证的中医护理) - LIU Xinying (刘新影); GUO Jing (郭敬); ZHANG Xinhong (张新红); YUAN Qiwei (袁奇伟) (中西医结合护理)
Objective To explore the effect of Traditional Chinese Medicine (TCM) nursing management for rheumatoid arthritis patients with damp-heat arthralgia spasm syndrome. Methods A total of 398 hospitalized patients with rheumatoid arthritis of damp-heat arthritis syndrome were selected. In addition to routine care, TCM nursing interventions such as Chinese herbal bathing, auricular point pressing therapy and cupping therapy were carried out. The symptoms such as joint swelling and pain, morning stiffness, fatigue and weakness were scored by digital scoring method on the day of hospitalization and the day before discharge. Results T scores of morning stiffness, joint swelling and pain, fatigue and weakness on the day before discharge were significantly lower than those on the day of admission, and the difference was statistically significant (P<0. 01). Conclusion TCM nursing based on syndrome differentiation can relieve the joint swelling, pain, morning stiffness, fatigue and weakness in patients with rheumatoid arthritis due to damp-heat arthralgia syndrome and improve their quality of life. (目的 探讨对类风湿关节炎湿热痹阻证患者采用中医护理干预的效果。方法 选取2019年1月—2020年12月医院收治的类风湿关节炎湿热痹阻证住院患者398例为研究对象, 在常规护理的基础上, 增加中药泡洗、耳穴贴压、拔罐治疗等中医护理干预。采用自身前后对照的方法, 采用数字评分法分别对住院当日和出院前1天患者关节肿痛、晨僵、疲乏无力等症状进行评分。结果 出院前1天患者晨僵、关节肿痛、疲乏无力等症状评分较入院当日明显下降, 差异有统计学意义(P＜0. 01)。结论 中医辨证施护可改善类风湿关节炎湿热痹阻证患者的关节肿痛、晨僵、疲乏无力等症状, 提高其生活质量。)